2000
DOI: 10.1016/s0092-8674(00)80873-9
|View full text |Cite
|
Sign up to set email alerts
|

6S RNA Regulates E. coli RNA Polymerase Activity

Abstract: The E. coli 6S RNA was discovered more than three decades ago, yet its function has remained elusive. Here, we demonstrate that 6S RNA associates with RNA polymerase in a highly specific and efficient manner. UV crosslinking experiments revealed that 6S RNA directly contacts the sigma70 and beta/beta' subunits of RNA polymerase. 6S RNA accumulates as cells reach the stationary phase of growth and mediates growth phase-specific changes in RNA polymerase. Stable association between sigma70 and core RNA polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
482
4
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(510 citation statements)
references
References 29 publications
22
482
4
2
Order By: Relevance
“…Nutrient limitation triggers alterations in the activity and promoter preferences of RNA polymerase, and major changes in the cell's gene expression program prime the cell for maintenance and survival rather than growth. 58 Several starvation-regulated factors can directly influence transcription by RNA polymerase, including the alarmone ppGpp (binding at the β′-ω and the β′-DksA interfaces of RNA polymerase), 59,60 the small RNA 6S (binding the σ 70 -RNA polymerase holoenzyme) 61,62 and a number of protein factors (DksA, 63 alternative sigma factors, 64 and anti-sigma factors 65 ) (reviewed in ref. 66).…”
Section: Why Degrade Trna?mentioning
confidence: 99%
“…Nutrient limitation triggers alterations in the activity and promoter preferences of RNA polymerase, and major changes in the cell's gene expression program prime the cell for maintenance and survival rather than growth. 58 Several starvation-regulated factors can directly influence transcription by RNA polymerase, including the alarmone ppGpp (binding at the β′-ω and the β′-DksA interfaces of RNA polymerase), 59,60 the small RNA 6S (binding the σ 70 -RNA polymerase holoenzyme) 61,62 and a number of protein factors (DksA, 63 alternative sigma factors, 64 and anti-sigma factors 65 ) (reviewed in ref. 66).…”
Section: Why Degrade Trna?mentioning
confidence: 99%
“…RNA was shown to regulate transcription and enhance long-term survival (Wassarman and Storz 2000;Trotochaud and Wassarman 2004).…”
Section: The (Nucleic) Acid Test For Functionmentioning
confidence: 99%
“…Hence, 6S RNA levels were determined during different stages of E. coli growth, taking into account the fact that this RNA is highly expressed in the stationary phase which is already known (Wassarman and Storz, 2000). After the purification process, the fractions of 6S RNA were further identified by reverse-transcription PCR.…”
Section: Identification Of the Purified Srna Speciesmentioning
confidence: 99%
“…The high structural similarity observed between 6S RNA and a DNA open promoter in RNA transcription process, as well as the identification of 6S RNA in a specific complex linked to RNA polymerase, has suggested that this RNA type functions by mimicking the transcription promoter. Hence, 6S RNA seems to directly compete with DNA promoters for the s 70 -RNA polymerase active site to inhibit the transcription process (Wassarman and Storz, 2000;Wassarman, 2007).…”
Section: Introductionmentioning
confidence: 99%